THE ROLE OF DIGITAL MATURITY IN THE KNOWLEDGE BASED ECONOMY - Nelson DUARTE; Carla PEREIRA; Ricardo SANTOS; Antonio AMARAL; Davide CARNEIRO (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2020)
Digital Transformation is a trend that goes beyond it and it is mandatory for organizations’ competitiveness. Digital Transformation is supported by information technologies, but aims to improve and optimize business processes in order to promote business success. In the present paper we start by fitting the concepts of digital transformation and knowledge-based economies (KBE), since both are supported by decision making processes based on data, information, and knowledge. Digital transformation processes might be seen as the micro level, while KBE the macro level. In order to foster KBE, organizations must work on their digital transformation and that can be a challenge in particular to SME. The present paper identifies the most relevant dimensions that must be considered to develop and apply a model to assess digital maturity. Along with these dimensions were also identified the main constraints faced by SME in the digital transformation process.